The Shaping of Form: Exploring Designers' Use of Aesthetic Knowledge. Issue 5 (June 2018) - Stigliani, Ileana; Ravasi, Davide
Research on design and designers has emphasized the tacit nature of the aesthetic knowledge that these professionals draw upon to make decisions about formal properties of objects and spaces, but is less clear about how design teams address the difficulties associated with expressing and sharing this type of knowledge. A ten-month ethnography in a design consultancy revealed a range of multimodal and cross-modal ways in which members of a design team compensate their imperfect capacity of articulating verbally their aesthetic knowledge in order to enable creative collaboration. In so doing, our study offers two main contributions. It illuminates the interplay between designers' aesthetic experiences, visceral responses and intuitive cognitive processes that enable designers to draw upon their aesthetic knowledge to support the collective accomplishment of their task, and provides an interpretation of the design process as a form of 'creative' intuition driven by emotional reactions to environmental stimuli and emerging formal solutions.